Effectiveness of Legal Aid in Religious Courts - Ishak, Nurfaika; Erlina, Erlina; Sari, Nila Indah (Faculty of Law, Mulawarman University, 2024)
The implementation of legal aid is one form of recognition and protection of human rights so that the need for access to justice and equality before the law can be realized. This study aims to analyze the role of legal aid institutions in religious considerations for the underprivileged and to analyze the phenomenon of supporting factors and factors that hinder the effectiveness of the implementation of the role of legal aid institutions. The approach used in this study is the legal approach because it will examine the role of legal aid institutions based on laws and regulations. The implementation of legal aid by Posbakum at the Religious Court of Selayar Islands Regency can be categorized as effective because in the last 3 years it has reached above 80% of the total number of cases received by the Court. The supporting factors for the implementation of legal aid include: the existence of regulations that serve as guidelines for implementation, the availability of adequate facilities, the establishment of cooperation between legal aid institutions, public trust, and the existence of a circuit court mechanism. Meanwhile, obstacles in the implementation of legal aid are limited resources, limited budget, and limited access for the community. The follow-up is the need to increase the quantity of human resources and increase the amount of the legal aid budget, as well as the need to carry out socialization of the existence of legal aid institutions so that the community becomes familiar with the tasks and functions of legal aid posts in the field.